2020
DOI: 10.1088/2053-1591/ab66ec
|View full text |Cite
|
Sign up to set email alerts
|

Key advances in development of straw fibre bio-composite boards: An overview

Abstract: In recent years, considerable attention have been given to the development and utilization of biodegradable fibres for bio-composite boards. This is due to the increase in the environmental consciousness and the need for sustainable development which enable establishment of new materials majorly for packaging, aircraft, furniture, and automobile. Straw fibres (wheat, rice, and corn fibre) are the most available natural agricultural wastes products, which has been utilized for the production of these new materi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 134 publications
(137 reference statements)
0
8
0
Order By: Relevance
“…The methods of straw management are characterized by certain limitations, hence, there is still a need to develop new methods and technologies for its use. The straw surplus can be successfully used in polymer composites [ 26 , 27 ]. Composites containing various types of plant fillers are produced on an industrial scale and continuous research results in the continuous expansion of the area of their application.…”
Section: Introductionmentioning
confidence: 99%
“…The methods of straw management are characterized by certain limitations, hence, there is still a need to develop new methods and technologies for its use. The straw surplus can be successfully used in polymer composites [ 26 , 27 ]. Composites containing various types of plant fillers are produced on an industrial scale and continuous research results in the continuous expansion of the area of their application.…”
Section: Introductionmentioning
confidence: 99%
“…61 However, ductile characteristics such as the microlayer and corrugated structure were observed in Figure 9(d) and, additionally, the appearance of voids and gaps in Figure 9(c) and (f) was due to interaction between fillers and matrix which made interfacial adhesion stronger, thus leading to cavitation of PVC particles. 55,62 Moreover, Figure 9(b) and (e) which correspond to 3% alkaline-treated, happened to resist more wear from SWC and SKC, and indicated that low alkaline concentration on SWC and SKC improve resistance to abrasive wear more than higher alkaline concentration treatment.…”
Section: Abrasive Wear Of the Compositesmentioning
confidence: 93%
“…Elementary straw fiber is comparable to wood fiber, and thus, pulping of straw to substitute wood fiber in the pulp and paper industry is an obvious opportunity, as is the production of nanocellulose . Further, composite boards of straw disintegrated to various stages embedded in a polymer matrix, or even binderless straw-based boards offer interesting opportunities. In terms of use as a structural material, the low-density straw and a low-wettability wax layer coating the epidermis present significant obstacles to the production of composite materials similar to important wood composites such as particle board or fiberboard. , Overall, this demonstrates the potential of straw to be a promising raw material for producing various materials with a wide range of properties.…”
Section: Introductionmentioning
confidence: 99%